Modulatory Effects of Betaine on D-Galactose-Induced Aging-Related IL-6 and TNF Inflammatory Mediators during Pregnancy in Rats - Jaber, Ali Habeeb (American Journal of Biomedicine and Pharmacy, 2025)
Age-related illnesses are aggravated by inflammation caused by aging. However, pregnancy introduces a new level of physiological complexity, which might exacerbate inflammatory responses. This study investigated the impact of betaine on the expression of TNF-α and IL-6, two key inflammatory mediators, in pancreatic tissue of pregnant rats with D-galactose-induced aging. We examined utilizing real-time quantitative PCR, looking at To imitate the consequences of aging, we evaluated changes in IL-6 and TNF using a D-galactose model. In pregnant rats' pancreatic tissue, D-galactose treatment significantly increased IL-6 and TNF-e expression levels when compared to untreated controls. Pregnant rats' pancreatic tissue showed significantly higher levels of IL-6 and TNF-α compared to untreated controls. Giving betaine significantly reduced these increases, returning IL-6 and TNF-α levels near to the control group. This shows that, in situations such as aging and pregnancy, betaine may operate as an inflammatory regulator. These findings suggest that betaine could be useful as a drug to help older women who are pregnant manage with the associated increased inflammation. Although these findings are encouraging, additional research is needed to discover exactly how betaine protects and what long-term implications this has for dealing with inflammation-related disorders during pregnancy and in old age.